2013
DOI: 10.1364/oe.21.009584
|View full text |Cite
|
Sign up to set email alerts
|

Sub-micrometer soft lithography of a bulk chalcogenide glass

Abstract: Abstract:We demonstrate, for the first time, time-and cost-effective replication of sub-micrometer features from a soft PDMS mold onto a bulk chalcogenide glass over a large surface area. A periodic array of submicrometer lines (diffraction grating) with period 625 nm, amplitude 45 nm and surface roughness 3 nm was imprinted onto the surface of the chalcogenide AsSe2 bulk glass at temperature 225°C, i.e. 5°C below the softening point of the glass. Sub-micrometer soft lithography into chalcogenide bulk glasses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…On the basis of this result, it was inferred that transferability in this kind of imprinting technique was limited to a few micrometers in the vertical direction. In fact, this behavior was already observed in previous works [4,14]. In order to investigate the transferability in the vertical direction in more detail, we made use of another quasi-three-dimensional pattern, i.e., an array of inverted four-story pagodas (Fig.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…On the basis of this result, it was inferred that transferability in this kind of imprinting technique was limited to a few micrometers in the vertical direction. In fact, this behavior was already observed in previous works [4,14]. In order to investigate the transferability in the vertical direction in more detail, we made use of another quasi-three-dimensional pattern, i.e., an array of inverted four-story pagodas (Fig.…”
Section: Resultssupporting
confidence: 63%
“…Based on our preliminary experiments performed to set suitable imprinting conditions, i.e., temperature, duration and displacement, imprinting at 255 • C resulted in a best performance. This temperature corresponded to a viscosity of ∼10 8 Pa s for As 2 S 3 glass [13], which belonged to the typical viscosity range previously suggested for imprinting this group of chalcogenide glass [1,3,14]. For all of the imprinting experiments in this study, temperature was thus fixed at 255 • C, but duration was allowed to vary typically from 600 s to 1800s according to geometry of the patterns.…”
Section: Methodsmentioning
confidence: 76%
“…6. The absorption peak at ~2.9 µm is due to the OH impurity in the glass, and another absorption peak at ~12.7 µm exists because of Se-OH bonds 40 . The confinement losses of the fundamental mode have been obtained at various core sizes of the fiber varying from 7 µm to 15 μm.…”
Section: Fiber Fabricationmentioning
confidence: 99%
“…[5][6][7] Although hot embossing or laser inscribing of these microstructures are well established techniques for bulk ChG in order to demonstrate the feasibility of these methods, patterning of thin lms has received more interest recently since typical required heights of these structures is only a few micrometers. [7][8][9][10][11] Earlier, these thin ChG lms were created with thermal evaporation mostly, but now solution processed ChG lms are beginning to show signicant advantages on lms deposited thermally. 1,2,[12][13][14][15][16][17][18][19][20][21][22] It has been shown that various amine solvents dissolve ChG via nucleophilic substitution of sulphide or selenide units with amine groups and may prove to be ideal for creating thin lms and structures for photonic, electronic or imaging application.…”
Section: Introductionmentioning
confidence: 99%